Potency of Sago Palm as Carbohydrate Resource for Strengthening Food Security Program - Ehara, Hiroshi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
A new competition between biofuel production and food production has occurred in recent years, therefore the development of some new plant resources and their utilization are needed. Sago palm and related species that can store a large amount of starch in the trunk and can grow under severe environmental conditions are considered to be potential starch resources for not only food production but also ethanol production. However, even sago palm, an elite species among the starch producing palms, grows under semi-domesicated or natural condition and there are many problems to utilize it. Thus, the systematic, ecological, physiological, agronomic and economic studies should be carried out for improvement of these species. Here, the recent research progress is reviewed. Large variation in morphological characteristics and palm size existed among the folk varieties of sago palm, and the difference in pith dry-matter yield was mainly attributable to trunk diameter and dry-matter content of the pith. The two key parameters were closely related with soil profile indicating natural fertility. On the other hand, the genetic distance of sago palm individuals grown in the Malay Archipelago was considered to be related to geographical distribution. The genetic variation was small in the western area and large in the eastern area. Sago palm tolerated up to 171mM (1.0%) NaCl concentration in the growth media for comparatively long period. The salt resistance of sago palm might be due to salt avoidance to mechanically restrict an excess of Na distribution from the roots to leaflets. The Na influx might be disturbed by the endodermal cells of roots even under 342mM (2.0%) NaCl condition. Sago palm tolerated severe low pH condition such at pH 3.6 in the growth media for 5 months at least and maintained a low Al3+ concentration in the plant tissues. Sago palm was considered to have a high tolerance to Al with the Al exclusion ability. Moreover, the growth of sago palm was stimulated when AlCl3 was added into the growth media with 10ppm Al. These physiological information on the growth response of sago palm to environmental stresses will be valuable for investigating concrete strategies to introduce new plant resources to barren lands with sterile soil and produce economic plants from poor productivity lands. Key words: acid soil, biofuel, genetic variation, Metroxylon, salt stress, starch